Syringomyelia with irreducible atlantoaxial dislocation, basilar invagination and Chiari I malformation - Wang, Shenglin (Springer-Verlag, 2009)
A 27-year-old woman presented with bilateral weakness of her all extremities for 5 years. She had a spastic gait and was unable to ambulate without assistance. Neurologic examination revealed increased deep tendon reflexes and positive pathologic reflexes. Radiographs showed occipitalization of the atlas, C2–C3 congenital fusion and fixed atlantoaxial dislocation with an atlanto-dental interval of 10 mm. MRI demonstrated cervicomedullary junction (CMJ) compression from the odontoid, a Chiari type I malformation, and syringomyelia extending from the foramen magnum to C5. The patient underwent transoral atlantoaxial release followed by posterior internal fixation from the occiput to the axis, which resulted in a significant improvement in motor function in all extremities. Post-operative images showed anatomical reduction of the atlantoaxial joint. However, an MRI performed 8 days following surgery showed a new retro-odontoid pannus had developed that was compressing the spinal cord at CMJ. A follow-up CT scan performed at 6 months post-operatively demonstrated a solid bony fusion between the occiput and C2, while an MRI at that time showed complete resolution of the retro-odontoid soft tissue mass with correction of the Chiari I malformation, and resolution of the syringomyelia. Final follow-up at 2-years revealed an excellent clinical outcome.